Dentigerous Cysts of Maxillofacial Region– Clinical, Radiographic and Biochemical Analysis - Sridevi, K; Kaushik, A; Ramaswamy, P; Manjula, M; Vinod, VC; Aravinda, CarlosK (Kathmandu University Medical Journal, 2015)
Background Dentigerous cyst is the second most common type of odontogenic cysts that encloses the crown of an unerupted tooth by expansion of its follicle due to the collection of cystic fluid. In view of the capability of these lesions attaining a marked size if not diagnosed early and treated properly, the present study was done based on the clinical and radiographic presentation of the dentigerous cyst in addition to the analysis of the cystic contents. Objective The present study reported 14 cases of dentigerous cysts (DC) with their incidence and relative distribution of the maxillofacial region along with the clinical and radiographic features and biochemical analysis of cystic fluid. Method The study was conducted at Sri Govind Tricentenary Dental College, Hospital and Research Institute, Gurgaon, Haryana for a period of one year and six months. A detailed case history and thorough clinical examination was done for the patients who were provisionally found to have odontogenic cysts. Necessary radiographs, aspiration of the cystic fluid and incisional biopsy were performed to the 14 patients who were provisionally diagnosed with dentigerous cysts (DC) after obtaining the informed consent and the cystic fluid was subjected to biochemical analysis. Results Majority of the affected patients with DC were in their second decade and showed more predilection for mandible with a male predominance. The area of predilection was third molar region in the mandible and it is the canine region in maxilla. All the cases were associated with impacted teeth and majority showed expansion of the buccal/labial cortical plate. The various biochemical variables (total protein content, albumin, globulin and albumin: globulin ratio) were also assessed in the present study. Conclusion The awareness of protean features of DC evident through this study is essential for the general as well as specialty practitioners for the accurate diagnosis and proper treatment planning of these non cancerous but potentially destructive lesions and also opens new avenues for further research. Kathmandu University Medical Journal Vol.13(1) 2015; 8-11